First successful pregnancy on peritoneal dialysis in Reunion island - Ali Aizel; Asma Omarjee; Delphine Hebmann (RDPLF, 2023)
We report the first successful pregnancy on peritoneal dialysis (PD), in 2023, in the overseas territories and departments (DOM-TOM) of France, in LA REUNION island, in a 34-year-old woman, a nurse by profession. She had been treated with continuous ambulatory peritoneal dialysis (CAPD) since February 2022. The original nephropathy was Alport syndrome. Pregnancy began twenty months after the start of dialysis. The patient wished to continue her pregnancy in CAPD in order to carry out exchanges during the day in her office, so as to be more available to her family in the evening. The first trimester of pregnancy was uneventful. During this period, the patient was informed of the risks of pregnancy, and together we defined our objectives with the means available. Adjuvant drug prescriptions (calcium, aspirin, iron, folic acid, vitamin D, etc.) were adapted during the second trimester, as was the PD protocol, in line with defined objectives. The third trimester required largely hospital-based management. Infusion volumes were progressively reduced, while the frequency of infusions was increased, thereby increasing the total daily volume of dialysis.  Residual renal function remained stable throughout the pregnancy, and plasma urea levels were kept below 20 mmol/L. She was delivered by Caesarean section under spinal anaesthesia at 33 weeks and 4 days of amenorrhea, with the birth of a 1,800g boy with Apgar coefficients of 5 at 1min, 8 at 3min and 9 at 5min. The baby's development and growth were very satisfactory. Respect for the patient's choices, her autonomy and her participation in the treatment were decisive factors in the success of the procedure.